2015
DOI: 10.1099/vir.0.000051
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and characterization of novel epitopes of serotype A foot-and-mouth disease viruses circulating in East Africa using site-directed mutagenesis

Abstract: Epitopes on the surface of the foot-and-mouth disease virus (FMDV) capsid have been identified by monoclonal antibody (mAb) escape mutant studies leading to the designation of four antigenic sites in serotype A FMDV. Previous work focused on viruses isolated mainly from Asia, Europe and Latin America. In this study we report on the prediction of epitopes in African serotype A FMDVs and testing of selected epitopes using reverse genetics. Twenty-four capsid amino acid residues were predicted to be of antigenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…2 D) and could explain the inability of the antisera to cross-react with the field isolates, and are probably the sites prone to change to help the virus escape immune pressure. Out of these, VP2-191 has been reported to be part of a neutralising epitope (antigenic site-2) both in serotype O and A FMDV [9] , [10] . Further, epitopes involving antigenic site 2 have been reported to be dominant within polyclonal responses of vaccinated animals [11] .…”
Section: Resultsmentioning
confidence: 99%
“…2 D) and could explain the inability of the antisera to cross-react with the field isolates, and are probably the sites prone to change to help the virus escape immune pressure. Out of these, VP2-191 has been reported to be part of a neutralising epitope (antigenic site-2) both in serotype O and A FMDV [9] , [10] . Further, epitopes involving antigenic site 2 have been reported to be dominant within polyclonal responses of vaccinated animals [11] .…”
Section: Resultsmentioning
confidence: 99%
“…Of these, VP2 133 has never been reported to be of antigenically important, however it is located close to VP2 134 that has been reported to strongly influence the binding of neutralising antigenic site 2 mAbs in serotype O FMDV [13] . Similarly VP2 191 has been recently shown to be linked to serotype O and A antigenic site 2 using a reverse genetics approach [33] , [34] . VP1 45 involving antigenic site 3 and VP1 137–141, 197 involving antigenic site 1 have been reported to be critical in serotype O mar-mutant studies [27] , [35] .…”
Section: Genetic Characterisation Of the Serotype O Virusesmentioning
confidence: 99%
“…Improved vaccines and vaccine strains are acutely needed in much of Africa, but their development has been hindered by a lack of definition of key parameters of circulating viruses. Recent work has investigated the relative antigenic significance of epitopes in African serotype A FMDVs (Bari et al., ). These data lead on from previous research by the same group that showed existing serotype A vaccine strains protected against only 5–46% of 56 East African field strains assessed and enabled identification of a candidate strain with broader vaccine match (Bari et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%